A highly sensitive photoinitiating system based on pre-associated ion-pairs for NIR radical photopolymerization of optically clear materials. Issue 47 (13th September 2022) - Zhou, Junyi; Pitzer, Lena; Ley, Christian; Rölle, Thomas; Allonas, Xavier
Abstract : A highly sensitive NIR photoinitiating system based on dye/borate associated pairs. Abstract : A new highly reactive photoinitiating system based on a penta-methine cyanine dye and a triarylalkylborate salt for radical photopolymerization reactions using near infra-red (NIR) light was investigated. The remarkably high reactivity is partly ascribed not only to the photochemical properties of the dye such as its very high absorption coefficients but also to the combination of the dye with the borate salt. Interestingly, the correlation between the borate salt concentration and the rate of polymerization can be displayed in a saturation graph. This effect is presumably caused by the formation of an ion-pair complex consisting of the cationic dye and anionic borate molecule in a medium of moderate polarity. It is shown that the association constant of such ion-pairs is quite high and, due to the short lifetime of the excited state of the dye, it is the only possible route for the generation of initiating radicals after excitation. Finally, it is found that the rate of polymerization correlates with the calculated rate of initiation, giving confidence to the proposed initiation mechanism. Advantageously, the high sensitivity of the new photoinitiating system allows for the use of a low LED light power of 40 mW cm −2 and thus supports a truly photonic mechanism of initiation instead of a thermal one.